2016
DOI: 10.1590/0034-7167.2016690313i
|View full text |Cite
|
Sign up to set email alerts
|

Notificação de problemas de saúde em trabalhadores de enfermagem de hospitais universitário

Abstract: Objective: to identify the health problems of nursing workers and describe their consequences. Method: an epidemiological, descriptive study with a quantitative approach. The survey was conducted through the Health Monitoring System for Nursing Workers (SIMOSTE) in three university hospitals in São Paulo within a 12-month period. Results: a total of 970 records related to health problems were identifi ed; most of these were related to sick leave, occupational accidents with leave, absences, and occupational ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
18

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 12 publications
0
17
0
18
Order By: Relevance
“…Corroborating with these data, a study (12) with nursing workers identified that among the reports of diseases of the respiratory system, influences, airway infections, tonsillitis and acute sinusitis are mentioned. Infectious and parasitic diseases include infectious diarrhea and gastroenteritis.…”
Section: Discussionmentioning
confidence: 93%
“…Corroborating with these data, a study (12) with nursing workers identified that among the reports of diseases of the respiratory system, influences, airway infections, tonsillitis and acute sinusitis are mentioned. Infectious and parasitic diseases include infectious diarrhea and gastroenteritis.…”
Section: Discussionmentioning
confidence: 93%
“…For example, in Brazil, the NPs are part of one of the professional categories responsible for a large part of the social security benefits granted by the National Social Security Institute (INSS) (SANTOS; LIMA, 2012). More recent studies corroborate a large number of NPs who have health problems with medical leave, leave by occupational accidents, absences and work accidents without leave (COSTA;FELLI, 2005;GUIMARÃES;FELLI, 2016).…”
Section: Introductionmentioning
confidence: 59%
“…The work profile of NPs may compromise their physical and emotional health (COSTA;FELLI, 2005;MACPHEE;DAHINTEN;HAVAEI, 2017;RAMOS et al, 2014), and the level of impairment of their health may differ by their attributions or position (GUIMARÃES;FELLI, 2016). One of the consequences of this impairment of NPs health is a sedentary lifestyle (OLIVEIRA; NOGUEIRA, 2010), which aggravates the scenario and can turn NPs into a risk group to develop stress and other work-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…12 This diversity of actions and responsibilities may be contributing to the emergence of work-related diseases or even occupational diseases such as cardiopulmonary, infectious, parasitic or emotional and psychic disorders. 13 Despite the existence of a Health Monitoring System of the Nursing Professional that allows the quantification of the sickness of these workers through the Communications of Work Accidents and the work leave by a medical permit, 14 so, it is desired to get to know the established health promotion strategies towards nursing professionals.…”
Section: Introductionmentioning
confidence: 99%